Critical Roles of PIWIL1 in Human Tumors: Expression, Functions, Mechanisms, and Potential Clinical Implications - Dong, Peixin; Xiong, Ying; Konno, Yosuke; Ihira, Kei; Xu, Daozhi; Kobayashi, Noriko; Yue, Junming; Watari, Hidemichi (Frontiers in Cell and Developmental Biology, 2021)
P-element-induced wimpy testis (PIWI)-interacting RNAs (piRNAs) are a class of small non-coding RNA molecules that are 24-31 nucleotides in length. PiRNAs are thought to bind to PIWI proteins (PIWL1-4, a subfamily of Argonaute proteins), forming piRNA/PIWI complexes that influence gene expression at the transcriptional or post-transcriptional levels. However, it has been recently reported that the interaction of PIWI proteins with piRNAs does not encompass the entire function of PIWI proteins in human tumor cells. PIWIL1 (also called HIWI) is specifically expressed in the testis but not in other normal tissues. In tumor tissues, PIWIL1 is frequently overexpressed in tumor tissues compared with normal tissues. Its high expression is closely correlated with adverse clinicopathological features and shorter patient survival. Upregulation of PIWIL1 drastically induces tumor cell proliferation, epithelial-mesenchymal transition (EMT), invasion, cancer stem-like properties, tumorigenesis, metastasis and chemoresistance, probably via piRNA-independent mechanisms. In this article, we summarize the current existing literature on PIWIL1 in human tumors, including its expression, biological functions and regulatory mechanisms, providing new insights into how the dysregulation of PIWIL1 contributes to tumor initiation, development and chemoresistance through diverse signaling pathways. We also discuss the most recent findings on the potential clinical applications of PIWIL1 in cancer diagnosis and treatment.